ABOUT ISSUES OF SUBJEST OF A ROBBERY - Kozhantayeva Жаухар Кенесбаевна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
The article covers acute problems related to the subject of robbery. The article contains the analysis of oppinions existing in the Kazakhstan criminal law on this point. The author offers his vision of the subject of robbery